ANALYZING THE PRE-WRITING PROCESSES OF STUDENT-AUTHORED WRITINGS PUBLISHED IN MASS PRINT MEDIA - Mayke Melya Sari (Language and Education Journal, 2024)
This research was motivated by students writing published in mass print media. The researcher wants to find ways the students apply the pre-writing process in student publication in print media such as newspapers. This research is qualitative research with a case study method that aims to analyze and discover how the students apply the pre-writing process before publication. The researcher found two students had applied all the stages and one student had not fully applied all the stages in pre-writing. The stages that have been taken are choosing a topic and gathering ideas. Meanwhile, the steps that have not been applied are organizing ideas, defining a topic sentence, and outlining. The conclusion is the students applied all the stages and the students not fully apply the stages in pre-writing can both publish their writing in print media